Diversity of trees in two mountain sites of Arakan Valley, North Cotabato - Aranico, Edgardo C.; Guihawan, Jaime Q. (2009)
The study was conducted from April 23 to May 8, 2008 in Mt. Sinaka and Mt. Mahuson, Arakan, North Cotabato in order to assess the abundance and diversity of trees present along the two study sites using quadrat and transect methods. In Mt. Sinaka, Salasang, Arakan, North Cotabato, a total of 97 identified and 17 unidentified tree species in 69 genera and about 39 families were collected and recorded along the three sampling sites corresponding to the three elevation gradients. Across the three sampling sites, Shorea negrosensis Foxw. is the most dominant, followed by Shorea contorta Vid. Calculations using Shannon-Weiner Diversity Index (H') reveals that the tree vegetation on this site can be classified as highly diverse. A total of 79 identified and 16 unidentified tree species in 50 genera and 34 families were recorded along the three sampling sites in Mt. Mahuson, Ganatan, Arakan North Cotabato where Lithocarpus apoensis (Elm.) Rehd. is the most dominant and is of the highest value. The diversity value of trees in Mt. Mahusosn is considered as moderately diverse. Three species are classified as critically endangered species, 3 endangered, 13 tree species are vulnerable, and 1 species is under the wildlife species category based on the DAO 2007-01 List of Threatened and Wildlife Species.
Keywords: Trees; Mt. Sinaka (Brgy. Salasang, Arakan, North Cotabato); Mt. Mahuson (Brgy. Ganatan, Arakan, North Cotabato); Tree species; Mindanao studies